HARMONIZATION OF SCIENCE AND RELIGION IN THE CONTEXT OF MULTISTRUCTURAL SOCIETY: BUILDING TOLERANCE AND HARMONY (Islamic Studies Journal for Social Transformation, 2024)
In the era of globalization and a multi-structural society full of diversity, the relationship between science and religion is crucial in forming social and spiritual harmony. This article discusses how harmonization between science and religion can be realized in a pluralistic society that is vulnerable to identity conflict, discrimination, and intolerance. Through a descriptive qualitative approach based on literature studies, this article examines the views of thinkers such as Stephen Jay Gould, Ian Barbour, and M. Amin Abdullah, who support an integrative and dialogical model between science and religion. It is emphasized that science answers “how” the world works, while religion answers “why” life is meaningful. This study also formulates concrete strategies such as the development of an integrative curriculum, technology-based education, religious moderation classes, and socio-educational activities that instill Islamic values, Indonesianness, and scientific progress. It is hoped that the integration of these values ​​can strengthen tolerance, overcome multicultural challenges, and form an inclusive and harmonious society spiritually and scientifically.
Keywords: Harmonization; Science and Religion; Multicultural; Tolerance; Value Integration